Development of antimicrobial fabrics based on silver and copper nanoparticles - Norashikin, Mat Zain (2014)
With growing public unease surrounding the extent of microbial infections, there is a demand for antimicrobial materials including antimicrobial textiles. Nanotechnology has provided new solutions for the development of antimicrobial fabrics. In this study, nanoparticles of silver (Ag) and copper (Cu) and alloy nanoparticles of Ag and Cu (Ag/Cu) have been synthesized by reduction of their respective nitrates by ascorbic acid, using chitosan as a stabilising agent and microwave heating. UV-vis spectrophotometry indicated the presence of the alloy by a single peak (500 nm) for Ag/Cu nanoparticles, whereas mixtures of Ag and Cu nanoparticles (Ag+Cu) showed two peaks of 420 and 500 nm, corresponding to pure Ag and Cu nanoparticles respectively. Particle size is increased by increasing nitrate concentration and reducing the chitosan concentration; Surface zeta potentials were positive for all the nanoparticles and varied from +27.8 to +33.8 mV. Ag and Cu nanoparticles were shown to be spherical whilst the alloy nanoparticles had an irregular shape. Cu nanoparticles resulted in higher inactivation of bacteria such as Bacillus subtilis (B. subtilis), Escherichia coli (E. coli) and methicillin-resistant Staphylococcus aureus (MRSA) than did Ag nanoparticles at the same concentration. The effect was reversed when tested on nanoparticles of the same mean particle sizee w ith Ag nanoparticles emerging as. more effective. Bacterial inactivation increased with concentration Of chitosan and the metal concentration. The nanoparticles showed a more potent antibacterial effect than did ions of the same metal. B. subtilis was more susceptible than E. co/i which may be due to the differences in their cell walls structure. MRSA proved harder to inactivate than both B. subtilis and E. coli under identical conditions. Antifungal activity was significantly affected by the types of nanoparticles employed. Ag nanoparticles displayed higher inactivation than Cu ones. Alloyed nanoparticles demonstrated the highest inactivation against both bacteria and fungi. This constitutes clear evidence of an antimicrobial synergy between the Ag and Cu. Bacteria and fungi in contact with nanoparticle-impregnated fabrics were revealed by FEGSEM to have taken on ashrunken appearance. Nanoparticle-impregnated fabrics reduced microbial viability by 80-90%, but this decreased in relation to the number of washes the fabric was subjected to and indicated a leached out of the nanoparticles. Pre-treatment of cotton fabrics with tannic acid and citric acid enhanced the durability of the antimicrobial effect when washed and this increased with concentration of the acid. Citric acid treated fabrics showed higher durability than tannic acid treated fabrics. Log reductions of Trichophyton interdigitale (T interdigitale) were lower than those for B. subiilis, E. coli and MRSA at the same test conditions. The combination of nanoparticles with the antifungal drug fluconazole proved effective, and reduced the time necessary to eliminate the T interdigitale than either nanoparticles or fluconazole alone.